Islamic Work Ethics and Religious Based Recruitment as a Strategy to Reduce Turnover Intention - Fahrudin Hasbi; Nurhidayati Nurhidayati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to examine the model of decreasing turnover intention by proposing ta'awun behavior as the main capital, where the ta'awun behavior of employees will be formed if individuals have Islamic work ethics, are led by religious leaders and are recruited using a religious approach. This research is an Explanatory Research. The population in this study are employees of the three companies that are members of a group of companies engaged in the cardboard box industry. The total population of all group employees is 300 people. Large sample or sample size 100-200. In this study, the number of samples was 135 respondents, and the data was collected using a questionnaire method. Data analysis used correlation test and structural equation modeling using PLS (partial least square) type 3.3 software to analyze the data. The results of the study show that there is a significant influence of Ta'awun behavior on Turnover Intention, there is a significant influence of recruitment based religious on ta'awun behavior, there is a significant influence of Islamic Works Ethics on ta'awun behavior, and there is a significant influence of Spiritual leadership towards Ta'awun Behavior.